Reflections on Supervision in Music Therapy in the Context of Autism - Marsimian, Nuria Inés Alicia (Voices: A World Forum for Music Therapy, 2024)
This paper is related to aspects of supervision in music therapy, specifically focused on Argentine music therapists working in the context of autism. A supervision approach is described for music therapy in this context. Some reflections regarding the themes identified and worked on during the supervision process are presented. The reflections and guidelines are based on the author´s experience as a music therapist supervisor in this field. Acknowledgments I am very grateful to my colleagues from Argentina and Latin America for their trust in my contribution as a supervisor during the supervision process. Not only for their willing to improve their services and their professional role in this context, but for giving me the opportunity to grow and nurture myself as a professional and as a human being. Editor’s Note: The Article Editor thanks Alex Kratchman for their additional assistance with English-language editing. Resumen El presente escrito está relacionado con los aspectos de la supervisión en musicoterapia, específicamente focalizado en el trabajo clínico realizado por los/las musicoterapeutas argentinos/as actuando en el contexto del autismo. Se describirá un abordaje de supervisión en musicoterapia para este contexto. Se expondrán algunas reflexiones vinculadas a las temáticas identificadas y trabajadas con los/las musicoterapeutas durante el proceso de supervisión. Dichas reflexiones y lineamientos están basados en la experiencia de la autora, como supervisora de musicoterapeutas trabajando en este campo de aplicación. Agradecimientos Agradezco a los/las colegas de Argentina y Latinoamérica por su confianza en mi aporte durante el proceso de supervisión. No sólo por su búsqueda en mejorar sus servicios y su rol profesional en este contexto, sino por darme la oportunidad de crecer y nutrirme como profesional y como ser humano. Nota del editor: el editor del artículo agradece a Alex Kratchman su ayuda adicional con la redacción en inglés.